2016
DOI: 10.1371/journal.pone.0148316
|View full text |Cite
|
Sign up to set email alerts
|

No Fabry Disease in Patients Presenting with Isolated Small Fiber Neuropathy

Abstract: ObjectiveScreening for Fabry disease in patients with small fiber neuropathy has been suggested, especially since Fabry disease is potentially treatable. However, the diagnostic yield of testing for Fabry disease in isolated small fiber neuropathy patients has never been systematically investigated. Our aim is to determine the presence of Fabry disease in patients with small fiber neuropathy.MethodsPatients referred to our institute, who met the criteria for isolated small fiber neuropathy were tested for Fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…In this multicenter study of 155 Nordic patients with idiopathic SFN and mixed neuropathy, no definite FD and hATTR amyloidosis cases were identified. This result is concordant with earlier screening studies for FD and hATTR amyloidosis in patients with idiopathic SFN …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this multicenter study of 155 Nordic patients with idiopathic SFN and mixed neuropathy, no definite FD and hATTR amyloidosis cases were identified. This result is concordant with earlier screening studies for FD and hATTR amyloidosis in patients with idiopathic SFN …”
Section: Discussionsupporting
confidence: 92%
“…Two treatable, possibly underdiagnosed hereditary diseases, known to cause painful polyneuropathy with involvement of small fibers, are Fabry disease (FD) and hereditary ATTR (hATTR) amyloidosis . The results of previous screening studies of the 2 conditions have been inconsistent …”
mentioning
confidence: 99%
“…Another smaller study confirmed the presence of immunological abnormalities (eg, antinuclear antibodies, extractable nuclear antigens, and celiac autoantibodies), whereas diabetes, prediabetes, and hypertriglyceridemia were not associated with SFN . A large study demonstrated that the prevalence of Fabry disease is irrelevant in adult SFN patients, a finding that allows excluding this genetic screening in patients with confirmed diagnosis of SFN . Early degeneration of small nerve fibers can occur in the pre‐symptomatic stage of patients carrying transthyretin mutations, whereas patients with a symptomatic stage of familial amyloid neuropathy more likely present with a mixed neuropathy …”
Section: Epidemiologymentioning
confidence: 99%
“…158 A large study demonstrated that the prevalence of Fabry disease is irrelevant in adult SFN patients, a finding that allows excluding this genetic screening in patients with confirmed diagnosis of SFN. 159 Early degeneration of small nerve fibers can occur in the pre-symptomatic stage of patients carrying transthyretin mutations, 160 whereas patients with a symptomatic stage of familial amyloid neuropathy more likely present with a mixed neuropathy. 161 Even in patients with a known possible etiology, additional underlying causes can be found in 27% of patients.…”
Section: Underlying Conditions and Pathophysiologymentioning
confidence: 99%
“…However, among 457 patients with cryptogenic or diabetic neuropathy, sequence changes in these genes were no more common than among control populations . Other studies exploring the diagnostic yield of GLA sequencing for Fabry disease among patients with small‐fiber neuropathy have demonstrated an extremely low diagnostic yield . Even the clinical trial data from the confirmatory hTTR amyloidosis studies supports the rarity of this disorder.…”
mentioning
confidence: 99%